The Influence of Health Education Using Audio-Visual on Teenagers' Knowledge Regarding Teenagers' Sexual Behavior at SMA I Darus Salam Tapos West Java - Miranawati, Eka; Putri Azzahroh; Vivi Silawati (Rajaki of Tulip Medika Publisher, 2024)
Background:During adolescence, individuals cannot take full responsibility for the activities they do. Problems related to reproductive health that can occur during adolescence include pregnancy out of wedlock, rape, prostitution among teenagers, abortion, sexually transmitted diseases, sexual harassment and other sexual deviations such as promiscuity. Objective:To determine the influence of health education using audio visuals on adolescent knowledge regarding adolescent sexual behavior at SMAI Darus Salam Tapos, West Java. Methodology:The type of research used in this research is analytical descriptive with a one group pretest posttest approach. The population in this study was all 62 level X teenagers registered at SMAI Darus Salam. The sample uses total sampling. The instrument used in this research was a questionnaire containing adolescent knowledge regarding adolescent sexual behavior to be measured before providing the intervention and after providing the intervention. And test the hypothesis using the t test. Research result:It can be seen that the difference in adolescent knowledge regarding adolescent sexual behavior before and after being given the Health Education intervention using audio visuals with results tending to increase can be seen from the mean, median and mode values. The results obtained showed a significance level of ˂0.001, which means it is lower than 0.05, so the hypothesis is accepted. Conclusion:There is an influence of health education using audio visuals on adolescent knowledge regarding adolescent sexual behavior at SMAI Darus Salam. Suggestion:It is hoped that the results of this research can be used as a reference for further research supported by other sources, or can be used as a comparison to research on the influence of reproductive health education counseling using audiovisual media on subsequent adolescent sexual behavior.